Diversity and Oriented Synthesis of Clopidogrel Drug Derivatives - Tejeswararao, D. (Asian Journal of Chemistry, 2020)
An efficient synthetic route has been developed for the synthesis of new clopidogrel drug derivatives. Key step of this method is to replacement of mesyl protected alcohol group with various aliphatic amines in presence of base. Various clopidogrel drug derivatives have been prepared in good yields. All the new compounds were confirmed by spectral studies and mass analysis. The main advantage of the new synthetic route has low cost and is fit for industrial applications.